2015
DOI: 10.1155/2015/971474
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Microgravity: Critical Review on the Use of Random Positioning Machines for Mammalian Cell Culture

Abstract: Random Positioning Machines (RPMs) have been used since many years as a ground-based model to simulate microgravity. In this review we discuss several aspects of the RPM. Recent technological development has expanded the operative range of the RPM substantially. New possibilities of live cell imaging and partial gravity simulations, for example, are of particular interest. For obtaining valuable and reliable results from RPM experiments, the appropriate use of the RPM is of utmost importance. The simulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
182
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 175 publications
(185 citation statements)
references
References 32 publications
(53 reference statements)
1
182
0
2
Order By: Relevance
“…A part of the incubated cells detaches from the bottom of a culture flask and forms 3D aggregates like they are observed after spaceflights [2, 4, 5, 19]. Even though in contrast to a stay in space, sheer forces are produced on the RPM, multicellular spheroids and tubular structures are formed in both conditions [18-20]. …”
Section: Discussionmentioning
confidence: 99%
“…A part of the incubated cells detaches from the bottom of a culture flask and forms 3D aggregates like they are observed after spaceflights [2, 4, 5, 19]. Even though in contrast to a stay in space, sheer forces are produced on the RPM, multicellular spheroids and tubular structures are formed in both conditions [18-20]. …”
Section: Discussionmentioning
confidence: 99%
“…Samples are placed at the centre of the frames, where the generated motion pattern is designed to equally distribute the gravity vector spatially and temporally (the gravity mathematically averages zero) [33]. Because the constant reorientation of the gravity vector prevents biological systems to adjust to this force, their response is similar to the one achieved upon real microgravity exposure [16].…”
Section: Simulated Microgravitymentioning
confidence: 99%
“…In vitro experiments [13] and animal studies conducted during space flight [14,15] have shown degenerative biomechanical or biochemical effects of microgravity. To study microgravity on Earth, random positioning machines (RPMs) are commonly used [16]. Signs of IVD degeneration were observed in mice discs cultured in a rotary wall vessel bioreactor [17], although this was not the case with rat IVDs [18].…”
Section: Introductionmentioning
confidence: 99%
“…The exact function of the RPM used in this study has been described in detail elsewhere 13 . Briefly, an incubator had been installed on rotating frames.…”
Section: Random Positioning Machine (Rpm)mentioning
confidence: 99%